MALANG CERAMIC CRAFT CENTER DENGAN PENDEKATAN ARSITEKTUR REGIONALISME DI KOTA MALANG - Afidah Silmi; Suparno Suparno; Dyah Susilowati Pradnya Paramita (Universitas Sebelas Maret Surakarta, 2015)
Designing Malang Ceramic Craft Center in Malang City motivated by the potential of ceramics craft, which currently increasing, support the efforts of the Malang City government to raising tourism, as well as Malang as one of the producers of ceramics craft that do not have an adequate infrastructure of tourism education and marketing. The purpose of this architectural planning is to provide a place for tourist, so that they can fulfill the tourism needs and to give the information about ceramics craft, as well as to help raising the income of Malang City through the marketing of ceramics craft. The issue of the design are: how to build Malang Ceramic Craft Center with the application of Regionalism Architecture for the building planning. The approach used in determining the design is by using the concept of Regionalism Architecture which is applied in form and fasade building, the pattern of mass arrangement, as well as the material and structure building. The result obtained is the design of an education tourism facilities that is Malang Ceramic Craft Center with Regionalism Architecture approach, which can visible in the use of Javanese traditional rooftop, joglo, the use of building color as an adjustment with buildings around, the mass form in accordance with the mass form of Javanese building, the application of ceramics craft ornament on building, the use of sculpture in accordance with the material object symbol and the use of local material on building. Keywords: Ceramic Craft, Fasade Building, Local Culture. Regionalism Architecture, Tourism Facility.